(untitled) (Journal of Bangladesh Institute of Planners, 2010)
While metro schemes have been suitable investments for some western cities and some Asian cities, like Hong Kong and Singapore, they are not necessarily the most appropriate options for cities in developing countries. Although urban transport problems, like congestion and pollution seem to be similar everywhere, the suitability of a metro solution is more questionable for cities in developing countries owing to their distinctive social, economic and spatial characteristics, and their existing transport technologies and the travel habits of their inhabitants. A critical examination of such issues is undertaken for the proposed metro for Dhaka. The study concludes that due to high population densities, transport users favour metro rail construction. On the other hand, the existing spatial structure of the city, patterns of land use, economic aspects and existing trip characteristics suggest metro is an inappropriate choice. Journal of Bangladesh Institute of Planners, Vol. 3, Dec 2010, pp. 33-51